Relationship between tropical endemic limbo-conjunctivitis and intestinal helminths in a population of Cameroonian children - Christelle Domngang Noche; Pierre Rene Fotsing Kwetche; Thierry Tumameu; Ernest Tambo; Roger Moyou; Assumpta Lucienne Bella (Cogent Medicine, 2017)
Background: Tropical endemic limbo-conjunctivitis (TELC) is an allergic limbo-conjunctivitis, very common in children of tropical areas, and often characterized by ocular morbidity. Several studies were devoted to the study of the epidemiological and clinical aspects of TELC in Africa but in Cameroon, no study has ever been conducted on its association with intestinal helminths. The objective of our work was to investigate the association between TELC and intestinal helminths in pupils of Njombe–Cameroon. Methods: We conducted a cross-sectional study from January to September 2014. Random consecutive sampling was carried out. Selected pupils underwent a comprehensive eye examination, and their stool sample was examined using the KATO-KATZ technic to search for helminths eggs. Statistical tests were used for data analysis (p-value <0.05). Results: Two hundred and fifty-three students were enrolled. Thirty-six (14.2%) were affected by TELC. The average age of children with TELC was 9 ± 2 years (range: 4–13 years) with a male predominance (p = 0.001). Conjunctival hyperemia (88.9%) was the major clinical sign with a predominance of limbic clinical form (58.4%). The prevalence of intestinal helminths was 28.1% in the general population vs. 33.3% in participants with TELC. TELC was not associated with intestinal helminths. Conclusion: The prevalence of TELC (14.2%) is low in our study. Male sex was associated to TELC. The overall frequency of intestinal helminth infection was 28.1% and the one amongst patients with TELC was 33.3%. Despite the presence of intestinal helminth infection in our population, it was not associated with TELC.